Lessons Learned from the Forest, Climate and Communities Alliance - Boshoven, Judy (USAID, 2014)
The Forest, Climate, and Communities Alliance (FCCA) was an initiative funded by USAID’s Bureau for Economic Growth, Education, and the Envi ronment/Office of Forestry and Biodiversity (E3/FAB) under the USAID G lobal Development Alliance (GDA)1 between 2009 and 2013. FCCA was one of the first USAID-funded projects for reducing emissions from defores tation and degradation (REDD+). The Rainforest Alliance (RA) implement ed FCCA in Ghana and Honduras. Operating in two different contexts all owed FCCA to generate important lessons learned that may be useful as countries around the world search for approaches to prepare for and im plement successful REDD+ mechanisms. In 2013, as FCCA was coming to an end, USAID tasked the Measuring Impact (MI) initiative with an indepe ndent review to generate lessons learned from FCCA. In capturing and d isseminating lessons from the FCCA project, the Agency intends to cont ribute to the understanding of what may be effective, and under what c onditions, when promoting REDD+ in conjunction with forest and agricul tural product certification. MI is a five-year USAID project executed by the E3/FAB Office designed to improve the Agency’s practice of cons ervation by building USAID’s capacity to better design, manage, evalua te, and learn from biodiversity conservation initiatives. As such, MI was tasked with carrying out this review of lessons learned from FCCA while using RA’s general hypothesis as the basis to describe the proje ct and its lessons.